Generation of asymmetric incommensurable torque signals. (November 2019) - Kurmann, L.; Duarte, J.L.
Abstract: Asymmetric incommensurable torque signals can be achieved by exploiting magnetic nonpolar repulsion techniques, see also [1], aiming at designing kinetic energy harvester (KEH) systems. This paper confirms by using three different simulation methods that an asymmetric incommensurable torque signal is feasible to be reached, exploiting non-conservative magnet fields. All shown calculations are in full agreement with the classical Electromagnetic Theory. The first method (I) is based on time consuming full 3D FE generated torque and force signals. The second method (II) is using also FE generated torque and force signals, but they are calculated only in orthogonal directions, approximated with Fourier Series and normalized to provide 2D stiffness signals. The third approach (method III) focuses on filamentary current rings to calculate the magnetic field of permanent magnets (PM) to generate in a purely analytically way the same force and torque signals as in the previous methods. However, only speculation about the energy source as required to maintain the forecasted persistent torque can be given.